Land-Use and Land-Cover Change in Dhaka Eastern Region and Its Impact on Surface Run-off - Huq, Md Habibul; Rahman, Md Mafizur (MIST International Journal of Science and Technology, 2020)
The aim of this study is to identify the impending urbanization-led land-use and land-cover (LULC) change of Dhaka Eastern Region (DER) and assessing its impact on surface runoff. Remotely sensed image data and proposed land-use plans for DER is analyzed and mapped in this study to detect the changes of LULC. A faster pace of land transformation was observed during 2016-17 from unpaved to the paved surface. Four post-developed LULC scenarios were predicted from the classified Landsat imagery of 2016-17 with increasing imperviousness. Runoff was estimated by SCS-CN method integrating RS and GIS tools. LULC changes according to land cover classes were assimilated with the hydrologic soil groups and then runoff depths were estimated for annual rainfall events in DER. Like the slower trend of urbanization, area-weighted CN also increased slowly during 2016-17 but followed a moderate leap in RDP and scenario-1. However, CN dropped in scenario-2 mainly due to the change in land-cover by infilling of highly permeable hydrologic soils. Predicted scenario-3 and 4 resulted in higher CN respectively because of increasing imperviousness in LULC. Higher CN resulted in higher runoff and more drainage requirements. RDP scenario or the predicted scenario-1 with CN 84 is potentially a viable LULC option for DER by 2035 and beyond that may cause more than 30% to 50% runoff comparing to the representative 2010 LULC condition.